(untitled) (City: History, Culture, Society, 2023)
With the establishment of Soviet power, the transformation of urban settlements, deemed essential for Sovietizing society, was mandated by communist doctrine. The complexity of the situation stemmed from the fact that urban issues had never been developed by Marxist theorists before, so Soviet functionaries had to invent ways to manage cities on the fly. In the absence of city executive committees, power was vested in provincial/district executive committee officials who relied on simple decision-making tools, constrained by limited time and experience. Reshaping urban space to meet various criteria tailored to specific objectives proved advantageous. The concept of “urban space” encompasses its physical manifestation (territory, buildings, engineering, and transport infrastructure), social manifestation (practices of creating and using physical space, a distinctive urban lifestyle, and social relations), and imaginary manifestation (the image of the city). Prior to the revolution, the understanding of urban space was guided by a functional approach rooted in historical and cultural traditions, whereas the socio-functional viewpoint became predominant under the Soviet government. Extensive reshaping of urban space led to its Sovietization (mainly in its social and imaginary manifestations). This managerial practice is exemplified by Vinnytsia, a city not subjected to the intense experimental pressure experienced by the flagship cities of Soviet industrialization.